Identifying drug‐related problems during transition between secondary and primary care in New Zealand. (7th January 2013) - Maxwell, Kathryn; Harrison, Jeff; Scahill, Shane; Braund, Rhiannon
Abstract: Objectives: The purpose of this study was to identify the type and frequency of drug‐related problems (DRPs) that are encountered when dispensing secondary care prescriptions in community pharmacy. Methods: A cross‐sectional study was conducted attempting to recruit all patients presenting with secondary care prescriptions to a single community pharmacy in New Zealand over a 3‐month period. The DRPs were recorded to allow analysis of the types and frequencies of the problems seen. Key findings: During the 3‐month period 401 patients consented to participate and 840 prescription items were analysed. DRPs were identified in 20% of prescription items analysed ( n = 172), affecting 38% patients ( n = 155). Bureaucratic interventions concerning product availability and payment issues accounted for 55% and affected 11% of the prescription items analysed. The remaining 45% of DRPs concerned clinical and patient issues and affected 9% of prescription items. Conclusions: This study has shown that the secondary–primary interface is problematic with respect to DRPs. Although pharmacists are in a position to identify and act on these DRPs, access to basic patient notes such as a discharge summary and including pharmacists in the communication between secondary and primary providers should assist in achieving seamless care for the patient and help to identify and prevent DRPs.